2009
DOI: 10.1523/jneurosci.3890-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Promotes and Protects Nigrostriatal Dopamine Function via a UCP2-Dependent Mitochondrial Mechanism

Abstract: Ghrelin targets the hypothalamus to regulate food intake and adiposity. Endogenous ghrelin receptors [growth hormone secretagogue receptor (GHSR)] are also present in extrahypothalamic sites where they promote circuit activity associated with learning and memory, and reward seeking behavior. Here, we show that the substantia nigra pars compacta (SNpc), a brain region where dopamine (DA) cell degeneration leads to Parkinson's disease (PD), expresses GHSR. Ghrelin binds to SNpc cells, electrically activates SNpc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
266
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(291 citation statements)
references
References 48 publications
20
266
0
5
Order By: Relevance
“…Unilateral microinjection of ghrelin causes the contralateral posturing and anticatalepsy effect, which is likely resulted from enhanced dopamine release induced by ghrelin directly and further activates the pathway of basal ganglia from the ipsilateral cortex. This was ARTICLE further confirmed by our in vitro and in vivo studies that intracerebroventricular injection of ghrelin in rats produces a dramatic enhancement of dopamine turnover rate and dopamine release in the striatum, which is in accordance with the studies that intraperitoneal administration of ghrelin improves the impairment of rota-rod performance in mouse MPTP-induced PD models 49 by stimulating dopamine overflow or dopamine turnover in the nucleus accumbens 9,12,50,51 . All together, our findings show that ghrelin, via specific blockage of KCNQ channel function, can increase the firing of mesencephalic dopaminergic neurons and mediate anticataleptic effects.…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelinsupporting
confidence: 88%
See 1 more Smart Citation
“…Unilateral microinjection of ghrelin causes the contralateral posturing and anticatalepsy effect, which is likely resulted from enhanced dopamine release induced by ghrelin directly and further activates the pathway of basal ganglia from the ipsilateral cortex. This was ARTICLE further confirmed by our in vitro and in vivo studies that intracerebroventricular injection of ghrelin in rats produces a dramatic enhancement of dopamine turnover rate and dopamine release in the striatum, which is in accordance with the studies that intraperitoneal administration of ghrelin improves the impairment of rota-rod performance in mouse MPTP-induced PD models 49 by stimulating dopamine overflow or dopamine turnover in the nucleus accumbens 9,12,50,51 . All together, our findings show that ghrelin, via specific blockage of KCNQ channel function, can increase the firing of mesencephalic dopaminergic neurons and mediate anticataleptic effects.…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelinsupporting
confidence: 88%
“…It is mainly secreted from stomach 7 , with small amounts produced in the brain 11 . GHS-R is expressed in various brain areas including SNc, hypothalamus, ventral tegmental area and hippocampus where ghrelin directly modulates the neuronal activity 9,10,12,13 . In SNc, ghrelin electrically activates dopaminergic neurons, and increases dopamine concentration in the striatum 12 .…”
mentioning
confidence: 99%
“…In this regard, we envisage a particularly central role for the metabolism-controlling gut factor ghrelin (Tschöp et al, 2000) in modulating dopamine levels during situations associated with low blood glucose levels, including starvation. In fact, a recent study by Andrews et al (2009) has demonstrated that ghrelin promotes tyrosine hydroxylase gene expression in substantia nigra concomitantly to increasing dopamine concentration in striatum. In addition, Andrews et al (2009) have also shown that peripheral ghrelin contributes to the maintenance and protection of normal nigrostriatal dopamine function via UCP2-dependent mitochondrial mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study by Andrews et al (2009) has demonstrated that ghrelin promotes tyrosine hydroxylase gene expression in substantia nigra concomitantly to increasing dopamine concentration in striatum. In addition, Andrews et al (2009) have also shown that peripheral ghrelin contributes to the maintenance and protection of normal nigrostriatal dopamine function via UCP2-dependent mitochondrial mechanisms. More generally, the body of data produced by Horvath, Andrews, and colleagues (Andrews et al, 2008Horvath et al, 2009) indicates that, under conditions of excessively low blood glucose levels, increased ghrelin signaling may activate mitochondrial respiration and promote fatty acid oxidation in dopamine neurons as an alternative fuel source.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin may also exert developmental and organizational effects during perinatal life like blastocyst development, perinatal growth and neurogenesis 14 . In addition, ghrelin has neuroprotective effects such as promoting and protecting nigrostriatal dopamine function via mitochondrial mechanisms 19 . Ghrelin has been associated with many psychiatric symptoms and psychiatric diseases as well as psychotropic drug effects and side effects 14,16,[20][21][22] .…”
mentioning
confidence: 99%